Compassionate care in nursing: The role of simulation-based compassionate care on nurse's caring behavior, self-efficacy and compassion competency - Rasha Mohammed Hussien (22928179) (2025)
Background Compassionate care is essential for enhancing patient outcomes and satisfaction. Despite established positive outcomes, the effectiveness of simulation-based training in fostering compassionate behaviors among nurses remains underexplored. This study addresses this gap by evaluating the impact of simulation-based compassionate care training on nurses' caring behavior, self-efficacy and compassion competence. Aim This study aimed to evaluate the effects of simulation-based compassionate care training on nurses' caregiving behavior, self-efficacy and compassion competence. Methods A quasi-experimental design was employed with 100 nurses from the Medical City, Qassim University simulation center. Participants were recruited using convenience sampling and allocated to an intervention group, which received simulation-based training and a control group. Data were collected using standardized scales measuring caregiving behavior, self-efficacy and compassion competence before and after the training from November 2024 to January 2025. Results The intervention group exhibited significant improvements in caregiving behavior (from 44.2 to 77.32, p < 0.001), self-efficacy (from 21.16 to 33.72, p < 0.001) and compassion competence across its domains of communication, sensitivity and insight, with p-values indicating statistically significant changes. In contrast, the control group showed minimal changes across these domains, with p-values indicating no significant differences. Conclusion The findings highlight the effectiveness of simulation-based compassionate care training in enhancing nurses' caregiving behaviors, self-efficacy and compassionate competence. Integrating such training into nursing education is essential for improving patient care quality and fostering a compassionate healthcare environment. Other Information Published in: Nurse Education in Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nepr.2025.104470